Development of Adolescent Individual Attention Focus Abilities during Vocal Ensemble Sessions - Trubina, Irena; Sile, Maruta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In 21st Century, music playing as an activity for attention development is one of the direction in the fast developing field of research in music pedagogy. The issue of adolescent attention focus ability development is urgent both in psychology, as well as pedagogy and specifically in music pedagogy. With the use of digital tests (VTS - Vienna Test System), adolescent attention focus ability development was determined in dynamic during vocal ensemble sessions. Upon analysing the individual adolescent results, it was concluded that development of attention focus ability was observed for the majority of adolescents who actively took part in the vocal ensemble lessons performing the include attention focus ability development exercises that were created in line with the recommendations of psychology and pedagogy scholars.